Pengaruh Citra Merek dan Kualitas Produk Terhadap Keputusan Pembelian Pada Perumahan Pesona Kalangsuria Rengasdengklok Karawang - Anggi Fitriani Ramadani; Dadan Ahmad Fadili (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine, analyze and explain the effect of Brand Image and Product Quality on Purchase Decisions at Pesona Kalangsuria Housing in Rengasdengklok Karawang. This study uses quantitative methods of descriptive analysis and verification with a quantitative approach. The sample in this study amounted to 184 respondents using probability sampling technique, namely simple random sampling. The analytical technique used in this study is scale range analysis and path analysis using the Succesive Interval Method (MSI) and SPSS 25 Software. The results of descriptive analysis in this study, the results obtained the average value of the Brand Image variable, which is 692.4 occupies the agreed criteria, which means good, the Product Quality variable, which is 677.2 occupies the agreed criteria, which means good and the Purchase Decision variable is 704.2 occupies the agreed criteria which means good. The results of the verification analysis in this study, the correlation coefficient between Brand Image and Product Quality was 0.781, which means it has a strong, positive and significant correlation level. The partial effect of Brand Image on the Purchase Decision variable is 14.3%. Partial influence of product quality on purchasing decisions is 59.7%. The simultaneous influence of Brand Image and Product Quality on Purchase Decisions is 74% while the remaining 26% is the influence of other variables not examined.